PENGARUH STRATEGI PEMASARAN, PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TIKET KERETA API - Ary Subiyantoro; Retno Dwi Astuti; Himawan Agung Nugroho (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
The purpose of this study was to determine the effect of marketing, service and promotion strategies on the decision to buy train tickets at PT KAI DAOP VI Yogyakarta. Data collection techniques through interviews with data collection instruments in the form of a questionnaire. This study uses quantitative analysis techniques using validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, significance test (t test and F test). The results of the study obtained the results of the regression equation Y = -0.130 + 0.341 X1 + 0.396 X2 + 0.318 X3, which means that the influence of marketing, service and promotion strategies affects the decision to buy train tickets at PT KAI DAOP VI Yogyakarta.